The Effect of Electronic Properties of Anodized and Hard Anodized Ti and Ti6Al4V on Their Reactivity in Simulated Body Fluid. Issue 7 (1st July 2022) - Di Franco, F.; Zaffora, A.; Pupillo, D.; Iannucci, L.; Grassini, S.; Santamaria, M.
Abstract : The electronic properties of barrier and porous layers on Ti and Ti6Al4V were studied. Barrier anodic oxides grown to 40 V on Ti and on Ti6Al4V are both n-type semiconductors with a band gap of 3.3 eV and 3.4 eV respectively, in agreement with the formation of amorphous TiO2 . Anodizing to 200 V at 20 mA cm −2 in calcium acetate and β -glycerol phosphate disodium pentahydrate leads to the formation of Ca and P containing porous films with a photoelectrochemical behaviour dependent on the metallic substrate. A band gap of 3.2 eV and the flat band potential of −0.5 V vs Ag/AgCl were measured for the porous oxide on Ti, while optical transitions at 2.15 eV and a significantly more positive flat band potential were revealed for the porous oxide on the alloy. The different electronic properties were rationalized by taking into account the presence of localized states inside the gap, induced by incorporation of Al and V from the underlaying alloy during the hard anodizing process. These electronic properties are responsible of the reactivity of porous layer grown on Ti6Al4V alloy in simulated body fluid.